Typology and priority problems of the cattle production systems in Tepecoacuilco de Trujano, Guerrero, México - Ríos-Hilario, Josué Jonathan; Rojas-García, Adelaido Rafael; Maldonado Peralta, María de los Ángeles; Palemón-Alberto, Francisco; Vázquez-Villamar, Mirna; Espinosa-Rodríguez, Mariana (Ecosistemas y Recursos Agropecuarios, 2025)
The objective of this study was to define the typify and identify the problems in the cattle production systems in Tepecoacuilco de Trujano, Guerrero, Mexico. A total of 143 farmers were Interviewed, select at random, based upon the model for sampling from finite populations. The interview included the general characteristics of the livestock production unit and the herd, technology used, feeding and perspective of the problems that limit this activity. The agglomerative hierarchical grouping based on the first three main components and their correlation to the variables allowed the identification of three types of cattle farming: cattle farming specialized in the sale of fattened calves (EVE), dual purpose (EDP) and specialized in the sale of weaned calves (EVP). The EVE presented the best technological, economic and livestock feeding conditions compared to the other groups. The EDP has the highest number of animals per herd, however, both the calf:cow ratio, number of stallions and surface area was like EVP. The most important general problem was animal feeding and the least important was genetics. For the specific constraint, the price of inputs as well as the availability of forage obtained the same priority. The identification of the constraints on cattle production supported by the characterization and typification contributes to the knowledge of the dynamics of the livestock systems.